(3TQM GdTeGFd ddJQePjs - (3Rjf GdOjf YHO GdQDa GdefGhj,J (B1030 (3g` s; (3GdJQePj , CHh YjSi,J (B279 (3g` s ((3eMeO Hf eMeO GdeOfi s)
(3ChdgG (B:s
(3hHYO , aEf cJGH GdTeGFd cJGH hMjO ai HGHg hcGf eef JUOi dTQMg ehdGfG YUGe GdOjf GdESaQGjfi hJdG GdTgGH GHf NLQ GdgjKei aSCdfi HYV GdCaGVd Cf Cedi JYdjbkkG aGLHJg Edi Pdc s
(3BNQgG (B:s
(3hhGab GdaQGZ ef Pdc GdJYdjb SfI (B999 (3ef gLQI GdeHYhK dcGaI GdCfGe Ydjg CaVd GdUdGI hGdSdGe s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B322 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B104 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B6 - (3U (B519s
Keywords: (3GdJGQjNs